ANALISIS NILAI-NILAI PLURALISME DALAM BUKU PENDIDIKAN AGAMA ISLAM (PAI) UNTUK SEKOLAH MENENGAH ATAS - Tien Rohmatin (Religi: Jurnal Studi Agama-agama, 2016)
Radicalism and extremism conducted at recent time by young people have reduced a quality of democratic life in Indonesia. In fact, democracy requires similar human-rihgts dan freedom from threat and coercion, moreover in religious freedom. The involvement of young people in extremist conduct can be seen further from text-book of Pendidikan Agama Islam/PAI (Education of Islamic Religion/EIR) which is used in senior high school. The goal of this research is to describe definitions of toleration, harmony, and discrimination that are explained in EIR books, and is to explore theological bases used by the books, and how those topics are interpreted. This writing uses qualitative method by an approach of content-analysis towards the books. The definition of toleration, harmony and discrimination used in those books just emphasizes the relations of inter-religions and inter-cultures. No explicite explanation deals with the importance to build toleration and harmony of intra-religion which recently gains huge attention in Indonesians for this makes conflict. The Qur’ânic verses becoming theological basis are quoted and interpreted textually. Meanwhile, stories of conduct and model are focused on classical era, in which there is no story, conduct, model or example from cases taken from Indonesian contexts.